COVID-19 and Nutrition - Farah Tadros; Susannah Folsom; Jeanette Andrade (EDIS)
The purpose of this new 4-page publication of the UF/IFAS Food Science and Human Nutrition Department is to discuss remaining hydrated, foods to consume, and programs and resources that are available as one battles and recovers from COVID. Written by Farah Tadros, Susannah Folsom, and Jeanette Andrade. https://edis.ifas.ufl.edu/fs434